Rapid fluctuation of the vaginal microbiota measured by Gram stain analysis. Issue 4 (26th July 2010) - Brotman, Rebecca M; Ravel, Jacques; Cone, Richard A; Zenilman, Jonathan M
Abstract : Background: The aetiology of bacterial vaginosis (BV) remains unknown. Objective: To describe longitudinal changes in vaginal microbiota. Methods: Thirty-nine women (mean age 36.8 years; 22 (56.4%) African-American) self-collected vaginal specimens twice weekly for 16 weeks as part of a vaginal douching cessation study. In an analysis where each woman serves as her own control, conditional logistic regression was used to evaluate daily, time-varying factors associated with a woman's incident BV episode(s) as compared with her persistently BV-negative sample(s). BV was defined by a Nugent's Gram stain score ≥7. Results: 46.2% of participants had BV in the first 4 weeks of observation. Rapid fluctuation of vaginal microbiota was observed in 226 transitions to BV or spontaneous remission. Duration of BV was often short: 51% of the episodes lasted for only one sample interval (3 days). Among women who had at least one BV episode, the median number of episodes per woman was 8.7 (SD 7.4, range 1–22). Lubricant use 1 day before specimen collection (adjusted OR (aOR)=11.75, 95% CI 1.96 to 70.27) and rectal sex 2 days before (aOR=4.48, 95% CI 2.79 to 7.17) were associated with BV onset. Conclusion: Rapid fluctuation of the vaginal microbiota was seen. Longitudinal studies with long intervals between sampling are likely to miss episodes of BV. Recent report of lubricant use and rectal sex were associated with incident BV.